Constant load ergometer for evaluation of anaerobic performance. - Carrasco Sosa, S.; Gaitán González, M.; Yáñez Suarez, C.; González Camarena, R. (Revista Mexicana de Ingenieria Biomedica, 1989)
A Dovein bicycle ergometer was built, mechanically braking, which was adapted two photodetectors to record the speed of pedaling, and a potentiometer that measures pedaling, and a potentiometer that measures angular displacement of the pendulum. Both signals are acquired and processed in a microcomputer. The muscular power developed during a maximum effort of 15 s was calculated, at constant load, observing that the temporal course of this follows a defined pattern, whose analysis provides sufficient information for the evaluation of the anaerobic muscular performance.